2022
DOI: 10.3389/fpls.2022.959118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cold acclimation, deacclimation and reacclimation on metabolite profiles and freezing tolerance in winter wheat

Abstract: Global climate change will cause longer and warmer autumns, thus negatively affecting the quality of cold acclimation (CA) and reducing the freezing tolerance (FT) of winter wheat. Insufficient FT and fluctuating temperatures during winter can accelerate the deacclimation (DEA) process, whereas reacclimation (REA) is possible only while the vernalization requirement is unfulfilled. Six winter wheat genotypes with different winter hardiness profiles were used to evaluate the impact of constant low-temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…LT 30 (temperature, at which 30% of plants die) of six winter wheat genotypes, determined in our previous study [ 28 ], was used as an indicator of FT in winter wheat ( Figure S2 ). The significance of relationships between antioxidants, measured in leaf and crown tissue under two separate treatments, and FT throughout CA, DEA, and REA was determined ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…LT 30 (temperature, at which 30% of plants die) of six winter wheat genotypes, determined in our previous study [ 28 ], was used as an indicator of FT in winter wheat ( Figure S2 ). The significance of relationships between antioxidants, measured in leaf and crown tissue under two separate treatments, and FT throughout CA, DEA, and REA was determined ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…If the above-ground section of a winter type crop suffers freezing damage, the survival of actively dividing meristematic cells within the crown region ensures the eventual regrowth of the plant [ 42 ]. Our earlier study showed higher levels of amino acids, soluble carbohydrates, hexose phosphates, citrate, and malate in the crowns, compared to the leaves [ 28 ]. Therefore, the concurrently elevated concentration of NAD + further substantiates the increased metabolic activity within the crowns during CA, DEA, and REA, with the ultimate purpose of protecting the meristematic cells from freezing damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations